ACCEPTABILITY OF REDFLOWER RAGLEAF (CRASSOCEPHALUM CREPIDIOIDES) TEA INFUSED WITH MINT (MENTHA X PIPERITA) - B. Kacayon, Caryle Jane; B. Torio, Sherene; Pati, Georgia Lyn L. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This study explored the acceptability of Redflower Ragleaf (Crassocephalum crepidioides) tea infused with mint (Mentha x piperita). The primary objectives were to evaluate the tea's acceptance based on color, aroma, taste, body, and overall acceptability. Additionally, the study aimed to identify the most preferred treatment and to establish a cost analysis ensuring a profitable return on investment. The researchers employed a quasi-experimental research design to achieve these objectives. The findings indicated that treatment 1 was the most favored, excelling in color, flavor, aroma, and overall acceptability, with moderate to high approval ratings across all parameters. For the body, treatment 2 received the highest rating, closely followed by treatment 1. The conclusions underscored treatment 1's higher acceptability; however, further improvements were recommended to enhance its characteristics. It was suggested to conduct laboratory testing to confirm the product's safety and economic feasibility and to extend the investigation into the interaction effects of the ingredients. A comprehensive feasibility study was also recommended to provide an in-depth analysis of production costs and the capital required for commercializing the tea. Additionally, further research into packaging and branding was advised to ensure the product was market-ready.